Transcriptomic analyses of regenerating adult feathers in chicken. (December 2015) - Ng, Chen; Chen, Chih-Kuan; Fan, Wen-Lang; Wu, Ping; Wu, Siao-Man; Chen, Jiun-Jie; Lai, Yu-Ting; Mao, Chi-Tang; Lu, Mei-Yeh; Chen, Di-Rong; Lin, Ze-Shiang; Yang, Kai-Jung; et al.
Abstract Background Feathers have diverse forms with hierarchical branching patterns and are an excellent model for studying the development and evolution of morphological traits. The complex structure of feathers allows for various types of morphological changes to occur. The genetic basis of the structural differences between different parts of a feather and between different types of feather is a fundamental question in the study of feather diversity, yet there is only limited relevant information for gene expression during feather development. Results We conducted transcriptomic analysis of five zones of feather morphologies from two feather types at different times during their regeneration after plucking. The expression profiles of genes associated with the development of feather structure were examined. We compared the gene expression patterns in different types of feathers and different portions of a feather and identified morphotype-specific gene expression patterns. Many candidate genes were identified for growth control, morphogenesis, or the differentiation of specific structures of different feather types. Conclusion This study laid the ground work for studying the evolutionary origin and diversification of feathers as abundant data were produced for the study of feather morphogenesis. It significantly increased our understanding of the complex molecular and cellular events in feather development processes and provided a foundation for future studies on the development of other skin appendages.